The dawn of man - Wolf, Josef (New York : Abrams, 1978)
Discusses the evolution of man from his ape-like ancestors who roamed the earth 20 millions years ago.
Includes bibliographical references.
Keywords: Evolution; Human origins; Prehistoric peoples